Comparative analysis on universal primary education policy and practice in sub-saharan: the cases of Ghana, Kenya, Malawi and Uganda - Ogawa, K. Keiichi Ogawa; Nishimura, M. Mikiko Nishimura (Rotterdam: Sense Publishers, 2015)
This book contains a five-year research work conducted by a group of African and Japanese researchers who have developed an equal partnership and network to review the expansion of primary education, some policies prompting the free primary education intervention, and the challenges of implementation based on the case study of two districts in four countries, namely, Ghana, Kenya, Malawi, and Uganda. The first part discusses issues related to administrative, financial, and perceptive issues related to UPE policies in each country case, followed by the second part that focuses on quality of education and UPE policies
Includes bibliographical references and index
Keywords: Universal primary education--policy; Primary education Policy--Sub-Saharan